The Philosophical-Scientific Ground on Which Young Husserl's Mathematical Education Took Place - González, Fredy Enrique; Bicudo, María Aparecida Viggiani [UNESP] (My University, 2025)
Context: This research is situated within the field of Philosophy, aiming to highlight the philosophical-mathematical study carried out by the young Husserl. Objective: To analyze the philosophical-scientific-mathematical environment in which his initial studies in Mathematics took place. Justification: The importance of this study lies in the way Husserl has been recognized as the founding philosopher of Phenomenological Philosophy. Throughout his academic trajectory, he consistently engaged with Mathematics, dedicating himself to critically reflecting on the production of this science and its significance in the constitution of contemporary European science. Methodology: Theoretical study. Setting and Participants: Bibliographical study of Husserl, the founder of Phenomenological Philosophy. Data Collection and Analysis: Data collection was carried out through bibliographical research. Results: The rigor of Husserl’s mathematical, scientific, and philosophical education is emphasized, understood through: (a) his participation in the course taught by Weierstrass; (b) his doctoral work, in which he made theoretical contributions to the Calculus of Variations; (c) the work through which he achieved his Habilitation as a university professor, where he conducted a psychological analysis of the concept of number. This study constituted the prelude to his Philosophy of Arithmetic, in which he deepened his reflections on number and began his journey through the intricacies of Philosophy and Phenomenology concerning Mathematics and Logic, which he further developed in his Logical Investigations as well as in subsequent studies. This study highlights the absence of references to Edmund Husserl’s name in important and well-known texts on the History of Mathematics, despite his significant contributions within the field of Mathematics itself.
La Base Filosófico-Científica sobre la cual se produjo la Educación Matemática del joven Husserl
A Base Filosófico-Científica sobre a qual ocorreu a Educação Matemática do Jovem Husserl
Keywords: arithmetization of mathematics; crisis of the foundations of mathematics; George Cantor; Karl Weierstrass; Mathematical analysis